MO465: Molecular Mechanisms of Vascular Ageing in Children With Chronic Kidney Disease. (3rd May 2022) - Bartosova, Maria; Zhang, Conghui; Herzog, Rebecca; Bernardor, Julie; Wetzel, Charlotte; Marinovic, Iva; Du, Zhiwei; Damgov, Ivan; Schaefer, Betti; Melk, Anette; Klaus, Guenter; Cerkauskiene, Rimante; et al.
Abstract: BACKGROUND AND AIMS: Paediatric patients with chronic kidney disease (CKD) develop significant atherosclerosis and vascular calcifications until early adulthood. Largely devoid of confounding lifestyle related factors and underlying disease mostly limited to congenital abnormalities of the kidneys and urinary tract, these patients provide highly sensitive and specific information on early CKD-induced molecular mechanisms of vascular disease and on putative therapeutic targets. METHOD: Standardized omental and parietal peritoneal tissue samples from 95 non-CKD individuals [median age 9.2 (interquartile range, IQR 15), 110 children with CKD5 (median age 8.6 (IQR 12)] underwent digital histomorphometry. Omental arterioles microdissected from surrounding fat tissue underwent whole-exome and proteome analyses, followed by gene set enrichment and Ingenuity pathway analysis. Vascular calcification pathway analysis was performed for 370 biological processes and molecular functions associated with vascular calcification extracted from Gene Ontology database. Key regulated pathways were validated by quantitative immunostaining. The effects of uraemic toxins on endothelial integrity were studied in vitro in human umbilical arterial and vein endothelial cells in Transwells. RESULTS: Lumen to vessel diameter (L/V) ratio was reduced in patients with CKD5. Parietal peritoneal arteriole L/V ratio was 0.54 (0.2) versus 0.63 (0.1) in non-CKD controls, omental arteriole L/V ratio 0.58 (0.1) versus 0.76 (0.1) in controls (both P < 0.001), indicating significant CKD5 related vascular disease. These findings were independent of underlying disease entities and gender. The parietal peritoneal submesothelial space exhibited infiltration of single CD45 positive lymphocytes, mesothelial cells which had undergone epithelial-to-mesenchymal-transition, and isolated peritoneal fibrin deposits. Submesothelial TGF-ß induced pSMAD was 4-fold increased and IL-17A 2-fold, while VEGF was not different compared to non-CKD controls. Gene set enrichment analysis of omental arteriolar multi-omics identified enrichment of pathways including telomere extension by telomerase, chromatin histone methylation, actin cytoskeleton, integrin- and tight junction signaling, and focal adhesion in children with CKD5 children compared to controls (P < 0.05). Vascular calcification pathway analysis identified 16/370 pathways significantly enriched on arteriolar transcriptome (P < 0.01), related to Wnt signalling, extracellular matrix organization, complement activation, autophagy and ossification. Applying the same threshold on proteome level, 10 calcification-related arteriolar pathways were identified and included DNA damage, fatty acid metabolism, calcium ion binding, extracellular matrix organization and complement activation. In independent age-matched cohorts, CKD5 children had shorter endothelial telomere and less endothelial methylated histone 3. The endothelial complement system was activated and arteriolar actin cytoskeleton interacting proteins gamma actin and profilin-1 were reduced in CKD5, cofilin-1 remained unchanged. In vitro, methylglyoxal and 3.4-di-deoxyglucosone-3-ene reduced transendothelial resistance, increased endothelial monolayer permeability and induced cytoskeleton disassembly (zonula occludens-1 and F-actin). These effects were prevented by co-incubation with anserine, 3-methylhistidine and alanyl-glutamine, but not by carnosine, L-histidine, 1-methylhistidine and methyl-alanyl. CONCLUSION: CKD5 results in major vascular ageing already in early childhood. Multi-omics analysis of omental arterioles identified specific mechanisms of CKD-induced vascular ageing and of vascular calcification. Endothelial cell barrier integrity is impaired, and in vitro reversed by specific dipeptides.